2021
DOI: 10.1002/jcop.22728
|View full text |Cite
|
Sign up to set email alerts
|

Mattering in the community: Domain and demographic differences in a US sample

Abstract: Mattering is defined as experiences of feeling valued and adding value in different domains of life: self, relationships, work, and community. Mattering is a construct with great relevance across psychological and social issues. Research has suggested there may be value in understanding group differences in mattering. Following the recent validation of a scale which measures mattering across multiple domains of life (MIDLS), the present study analyzed a representative US sample to identify demographic group di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 78 publications
0
10
1
1
Order By: Relevance
“…Meanwhile, differences by gender and race/ethnicity varied by domain, demonstrating the utility of a multidimensional conception of mattering. These comparisons are investigated in greater statistical detail in Scarpa et al, (2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, differences by gender and race/ethnicity varied by domain, demonstrating the utility of a multidimensional conception of mattering. These comparisons are investigated in greater statistical detail in Scarpa et al, (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Full participant demographics along with means by group and subdomain are outlined in Table 1. Between-group comparisons are the subject of further analysis in (Scarpa et al, 2021).…”
Section: Participantsmentioning
confidence: 99%
“…This measure reflects the emphasis of mattering in terms of having value to others and giving value to others emphasized by Prilleltensky's description of the mattering construct (see Prilleltensky, 2020;Prilleltensky & Prilleltensky, 2021). Analyses of responses to this measure focused on community mattering established that higher levels of community mattering were reported by people who were employed and had higher socioeconomic status (Scarpa et al, 2021b). Also, respondents tended to report greater community mattering in terms of giving value than having value.…”
Section: The Assessment Of Matteringmentioning
confidence: 99%
“…Further, results that hold over a general population may not be true for particular groups within that population ( Rowe and Trickett, 2018 ; Buchanan et al, 2020 ). This is a meaningful concern given the demographic heterogeneity of the United States and prior findings that mattering levels vary within-country race/ethnicity, gender, age, and other demographic groups ( Scarpa et al, 2021a ). As such, focused studies exploring the experiences of marginalized and underrepresented groups should be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…First, cross-cultural literature has demonstrated variability with respect to related constructs, including sense of community ( Brodsky, 2009 ; Barbieri and Zani, 2015 ) and belonging ( Chiu et al, 2016 ). Additionally, several empirical studies have demonstrated the existence of within-country demographic group differences in mattering ( Scarpa et al, 2021a ), some of which point to the role of cultural elements such as religiosity ( Lewis and Taylor, 2009 ).…”
Section: Introductionmentioning
confidence: 99%